Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial Melalui Penerapan Model Problem Based Learning (PBL) Berbasis Zoom Meeting Di Kelas VIIIA SMP Negeri 2 Bangsalsari Jember - Indriastutik (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study is to describe the increase in Social Science learning outcomes after applying the Zoom Meeting-based Problem Based Learning (PBL) model in class VIIIA SMP Negeri 2 Bangsalsari Jember in the academic year 2020-2021 semester 2. The research design used is classroom action research (classroom action research) in two cycles. Each cycle consists of two meetings which include planning, action, observation and reflection. This research was conducted from January to February 2021. The data collection method used the test and observation method. The results of the research carried out concluded that the increase in Social Science learning outcomes after applying the Zoom Meeting-based Problem Based Learning (PBL) model in class VIIIA SMP Negeri 2 Bangsalsari Jember in the 2020-2021 Semester 2 academic year, amounted to 20.83% of completeness. classical learning outcomes, namely the percentage of completeness in the first cycle of 75% increased to 95.83% in the second cycle. Meanwhile, the students' average score was 13.75 from the first cycle average of 74.79 which increased to 88.54. In addition, the PBL learning carried out also increased student activity from the moderate category in the first cycle to the second cycle with the high category.